Moringa and Ricinus association potential in the sub-tropics of Veracruz - Valdés Rodríguez, Ofelia Andrea; Palacios Wassenaar, Oliva Margarita; Ruíz Hernández, Rafael; Pérez Vásquez, Arturo (Revista Mexicana de Ciencias Agrícolas, 2018)
This paper evaluates the establishment of an associated plantation of Moringa oleifera Lam. and Ricinus communis L. in eroded soils in the sub-tropics of Veracruz. The plants were established from seeds during the rainy season without irrigation or fertilizer. Development on the site was monitored for a period of 22 months, taking allometric monthly records, as well as their productivity since the beginning of its establishment. The results indicate a large capacity for survival of M. oleifera with respect to R. communis, while R. communis showed higher productivity during the first year. Both species survived the period of drought and poor soils of the region; however, they had low productivity and serious problems with insect pests. Investment costs for the first year were lower by 86% compared to regional crops such as sugar cane, although the benefit-cost ratio was only 7% of the benefit-cost. We conclude that we can recommend the establishment of this association, as long as advice for biologically control pests is guaranteed, increasing productivity and achieve sales of processed products.
Keywords: Moringa oleifera; Ricinus communis; cost- benefit; productivity; sub-tropical Veracruz